Shape and spin of asteroid 967 Helionape - Apostolovska, G.; Kostov, A.; Donchev, Z.; Bebekovska, E. Vchkova; Kuzmanovska, O. (Cambridge University Press (CUP), 2017)
Knowledge of the spin and shape parameters of the asteroids is very important for understanding of the conditions during the creation of our planetary system and formation of asteroid populations. The main belt asteroid and Flora family member 967 Helionape was observed during five apparitions. The observations were made at the Bulgarian National Astronomical Observatory (BNAO) Rozhen, since March 2006 to March 2016. Lihtcurve inversion method (Kaasalainen et al. (2001)), applied on 12 relative lightcurves obtained at various geometric conditions of the asteroid, reveals the spin vector, the sense of rotation and the preliminary shape model of the asteroid. Our aim is to contribute in increasing the set of asteroids with known spin and shape parameters. This could be done with dense lightcurves, obtained during small number of apparitions, in combination with sparse data produced by photometric asteroid surveys such as the Gaia satellite (Hanush (2011)).
Keywords: Minor planets, asteroids, photometric-Asteroids: individual: 967 Helionape